LHC dark matter signals from vector resonances and top partners - Belyaev, Alexander S. (2018)
Extensions of the standard model which address the hierarchy problem and dark matter (DM) often contain top partners and additional resonances at the TeV scale. We explore the phenomenology of a simplified effective model with a vector resonance Z′, a fermionic vectorlike colored partner of the top quark T′ as well as a scalar DM candidate φ and provide publicly available implementations in CalcHEP and MadGraph. We study the pp→Z′→T′T′̄→tt̄φφ process at the LHC and find that it plays an important role in addition to the T′T′̄ production via strong interactions. It turns out that the presence of the Z′ can provide a dominant contribution to the tt̄+ET signature without conflicting with existing bounds from Z′ searches in di-jet and di-lepton final states. We find that, through this process, the LHC is already probing DM masses up to about 900 GeV and top partner masses up to about 1.5 TeV, thus exceeding the current bounds from QCD production alone almost by a factor of 2 for both particles.